Pre-service teachers’ emotional intelligence and motivations for choosing a teaching career in Finland - Myrto Kyriazopoulou; Riitta-Leena Metsäpelto; Sotiria Varis; Joona Muotka (Cogent Education)
Emotional intelligence (EI) and the motivations behind choosing a teaching career are recognized as important factors in teacher education research. In this study, we aimed to explore the EI profiles of students at the beginning of their initial teacher education and the associations of EI profiles with these students’ motivations for choosing teaching as a career. We collected data from eight universities across Finland (N = 953) and used the Self-Rated Emotional Intelligence Scale (SREIS) and the Factors Influencing Teaching Choice scale (FIT-Choice). To identify EI profiles, we first performed a latent profile analysis (LPA). Next, to explore the relationships between EI profiles and various motivations for selecting a teaching career, we used the three-step and Lanza method. Four distinct EI profiles were identified from the LPA analysis and the results showed that students with high EI chose a teaching career based on social utility values.